Aprovechamiento de residuos plásticos (bolsas) en la producción de banano y plátano en la zona bananera (2020)
The objective of this research is to develop the process of recycling, collecting and transforming plastic bags in banana production, in the elaboration of new products for the daily use of homes, all this in order to minimize its environmental impact; It is remarkable how people have taken consumption habits not very responsible with the environment, supporting economic systems that are reflected in the contamination of our ecosystems and affect human health, the use of millions of plastic bags every minute in the world is has become one of the most important environmental problems of the current century, the methodology used has a qualitative approach because the physical properties of the resulting material are established through an analysis that determines the accessories to be made with this material, these data are obtained by Observation sheets, surveys, interviews that allow having a database with extensive knowledge to propose the best possible solution to the problem.